Bangsa Malaysia as a liminal identity in anthony burgess’ the Malayan trilogy - Abd Razak, Farahanna (2017)
Although widely known outside Malaysia for its literary depictions of the last days of the British Empire in the Malayan peninsula as the country struggles towards independence, The Malayan Trilogy (1964), consisting of Time for a Tiger (1956), The Enemy in the Blanket (1958) and Beds in the East (1959), is believed to have been overlooked and undermined in the Malaysian literary context. It is set in preindependence Malaya and was written by the contemporary British author, Anthony Burgess (1917-1993), with the central themes of clashes of religions, the colliding of cultures and identity conflicts, chronicling the lives of the Malayan society and how they cope with different elements that shape the nation prior to its independence. More significantly, the trilogy was inspired by Burgess’ own real-life experience when he worked in Malaya. Due to its themes of religion, ethnicity and identity, these issues highlighted by Burgess in the trilogy are examined in this study, because religion, in particular, has been identified as the main factor contributing to what is known as ‘liminal identity,’ as it provides one with the base for the development of secured identity and psychological stability. This study then aims to examine how the practices of Islam and the Malay culture by selected Muslim Malay characters are reflected by Burgess as part of the liminal aspects of the identity of Bangsa Malaysia and to discover the emerging patterns of the understanding of the identity of Bangsa Malaysia through Burgess’ portrayals of the selected Muslim Malay characters. Using a textual analysis as my methodology to address my research objectives, I utilised a combination of the concept of liminality (1967) by the British cultural anthropologist, Victor Witter Turner (1920-1989), together with my own understanding of the concept of Bangsa Malaysia, by focusing on dialogues, scenes and the narrative technique of the author as the omniscient narrator in the trilogy. My findings reveal that the Muslim Malay characters are divided into different conflicts based on each text; the Muslim Malay characters in Time for a Tiger live in a fusion of animistic and Islamic beliefs although they seem to be both overtly and obliquely aware of the incompatibility of such a way of life. On the other hand, in The Enemy in the Blanket, the Muslim Malay characters are found to be conflicted between living a Muslim way of life and the Westernised lifestyle. In contrast, the Muslim Malay characters in the third and last text, Beds in the East, are portrayed as being conflicted between two elements, namely their ethnicity, Malay, and the emerging patterns of a contemporary understanding of a national identity, Bangsa Malaysia. The findings of my study therefore may hopefully lead to a number of potential future research, namely on examining other Muslim non-Malay characters in the trilogy to enrich the scholarship on The Malayan Trilogy by combining Turner’s concept of liminality with the concept of Imagined Community (1983) by Benedict Anderson (1936-2015), and also through the combination of the concept of liminality and the model of the psyche by Sigmund Freud (1856-1939). In addition, the concept of Bangsa Malaysia can also be used to analyse non-Malay characters from other texts with Malayan/Malaysian settings.